A Decade of Robotic-Assisted Radical Nephrectomy with Inferior Vena Cava Thrombectomy: A Systematic Review and Meta-Analysis of Perioperative Outcomes. Issue 3 (1st September 2022) - Garg, Harshit; Psutka, Sarah P.; Hakimi, Abraham Ari; Kim, Hyung L.; Mansour, Ahmed M.; Pruthi, Deepak K.; Liss, Michael A.; Wang, Hanzhang; Gaspard, Christine S.; Ramamurthy, Chethan; Svatek, Robert S.; Kaushik, Dharam
Abstract : Purpose: Open radical nephrectomy with inferior vena cava thrombectomy (O-CT) is standard management for renal cell carcinoma with inferior vena cava thrombus. First reported a decade ago, robotic-assisted radical nephrectomy with inferior vena cava thrombectomy (R-CT) is a minimally invasive option for this disease. We aimed to perform a systematic review to assess the safety and feasibility of R-CT in terms of perioperative outcomes and compare the outcomes between R-CT and O-CT. Materials and Methods: The PubMed®, Scopus®, Cochrane Central Register of Controlled Trials and Web of Science TM databases were searched using the free-text and MeSH terms "renal cell carcinoma, " "inferior vena cava, " "thrombosis" or "thrombus, " "robot" and "thrombectomy." Studies reporting perioperative outcomes of R-CT and studies comparing R-CT with O-CT were included. The review was done in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Results: The search retrieved 28 articles describing R-CT, including 7 comparative studies. This systematic review included 1, 375 patients, out of which 329 patients were in single-arm studies and 1, 046 patients were in comparative studies. Of the 329 patients who underwent R-CT, 14.7% were level I, 60.9% level II, 20.4% level III and 2.5% level IV thrombus. Operative time ranged from 150 to 530 minutes; blood transfusion was administered in 38.2% (126). The overall complication rate was 30.3% (99). R-CT, in comparison to O-CT, was associated with a lower blood transfusion rate (18.4% vs 64.3%, p=0.002) and a lower complication rate (14.5% vs 36.7%, p=0.005). Major complication and 30-day mortality rates were similar in both groups. Conclusions: R-CT has acceptable perioperative outcomes in carefully selected patients. Compared with O-CT, R-CT is associated with a lower blood transfusion rate and fewer overall complications. In experienced hands with carefully selected patients, R-CT is feasible and safe, with acceptable outcomes; however, selection bias limits definitive inference of these results, and optimal patient selection criteria remain to be described.